Pengembangan Media Pembelajaran Augmented Reality dan Wordwall “Complete the Sentence” Tema Gegenstände in der Schule Untuk Keterampilan Berbicara Bahasa Jerman Fase F - Pregi Shinta Maharani; Dra. Fahmi Wahyuningsih, M.Pd (LATERNE, 2026)
This development research is motivated by the need for innovative learning media using interactive digital technology in German language learning at Phase F. This need was identified based on the results of interviews with a German language teacher at SMAN 1 Menganti. Based on this issue, the purpose of this study is to develop Augmented Reality learning media and Wordwall “Complete the Sentence” with the theme Gegenstände in der Schule for German speaking skills at Phase F. This study also aims to determine the feasibility of the developed Augmented Reality and Wordwall “Complete the Sentence” media. The research model used is Research and Development (R&D) by Dick and Carey. The stages of this research follow the ADDIE model, consisting of three stages: Analysis, Design, and Development. The data collection instrument used in this study is an expert validation sheet. The experts involved in assessing the feasibility of the media development are a material expert and a media expert. The results of the feasibility test show a percentage of 98.18% from the material expert and 90% from the media expert. Therefore, it can be concluded that the Augmented Reality learning media and Wordwall “Complete the Sentence” are highly feasible to be used as learning media for German language classes at Phase F. Keywords: Learning German, German as a foreign language, development of Augmented Reality and Wordwall “Complete the sentence” learning media, Phase F.